Rebranding Logo dan Citra: Upaya Pengembangan Usaha Kain Pantai Aussenchia - Wulandari, Riza; Tria Hikmah Pratiwi; Lilis Yuningsih; I Wayan Gede Lamopia (Insan Kreasi Media, 2024)
The development of society today requires an industry to transform to increase customer loyalty. Lack of understanding of the importance of branding is a minimal marketing problem. This community service activity aims to develop a business owned by a beach fabric home industry called Aussenchia. The object of this community service was carried out in Denpasar City, Bali Province within 8 months. This method of implementation applies participatory action research involving Aussenchia in determining the rebranding of the logo. The result obtained is the formation of a logo adapted from the Aussenchia motif in the form of simple strokes that are collected and arranged to form a repetitive pattern and the addition of the shape of the gate as a philosophy of opening fortune. This logo branding was then applied to the new Aussenchia packaging. The implication of this community service activity is to increase the novelty of marketing strategies used for beach fabric packaging. In addition, business actors in the household industry category can consider considering the importance of branding their business identity.